Socialization and training processing cooking oil waste (jelantah) on household scale - Jujun Ratnasari; Lela Mukmilah; Salsabilla Dwita; Siti Hanipah (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
Used cooking oil is still widely used by the general public, which can be harmful to health. Otherwise, it is typically disposed of directly into the environment, becoming a hazardous pollutant. This was necessary to provide knowledge about the dangers of used cooking oil to health and to train the community to reduce waste cooking oil pollution in the environment. The outreach provided information on the definition of used cooking oil, its contents, and the negative impacts of using used cooking oil on health. The training was conducted using the PRA method so that the community could directly practice processing used cooking oil for reuse. The effectiveness of the training was measured using questionnaires before and after the activity. The results of the questionnaire showed that more than 80% of participants agreed or strongly agreed with the statement that they really needed training and materials to process used cooking oil. More than 80% agreed and strongly agreed that this outreach and training should be expanded to other communities. Participants were very enthusiastic and have positive respons about recycling used cooking oil that they believed could provide economic benefits and reduce the amount of oil waste dumped into the environment